Healthy China 2030: how to control the rising trend of unintentional suffocation death in children under five years old - Fanjuan Kong; Lili Xiong; Aihua Wang; Donghua Xie; Jian He; Jinping Su; Kui Wu; Zhiyu Liu; Hua Wang (BMC, 2020)
Abstract Background To investigate the occurrence frequency, changing trends, and epidemiological distribution of unintentional suffocation in children under 5 years old. Methods The data were collected from the Maternal and Child Health Surveillance system from 2009 to 2018. The cause of death was classified by ICD-10. Data on unintentional suffocation death were calculated according to the characteristics of the population, time, space, cause of death and medical treatment, and constituent ratio were calculated. Results The mortality rate of children under 5 years old showed a downward trend, but the mortality of unintentional suffocation initially decreased and then increased. The death rate of unintentional suffocation in children less than 1-year-old was much higher than that in children aged 1 to 4 years old. The death rate of unintentional suffocation was higher in boys than in girls, and the rate was higher for rural children than for urban children. The number of low-weight and pre-term infants in the group under 1-year-old was significantly higher than that in the group of 1-4 years old. Children under 1-year-old are more likely to die at home than children aged 1 to 4 years old, and a higher proportion of younger children did not receive treatment. More than 80% of children under the age of 5 go untreated because it was too late to go to the hospital. Conclusion For areas and populations with a high incidence of unintentional suffocation, we suggest that priorities should include prevention, the development of a safe environment, strengthened prevention, the development of safety habits, and the popularization of first aid knowledge.